Indexes and indexing : Nigerian perspectives - Nigerian Library Association (Lagos : Nigerian Library Association, 1987)
The papers in this volume were presented during the 1984 Seminar/Workshop on indexing. The seminar was one of the effective means of satisfying the need for continuing education for Library professional practitioners.
Being selected papers from a seminar on indexing services, organised by the cataloguing and classification section, Nigerian Library Association, 23-25 July, 1984.
"Held at the University of Jos, Plateau State July 23-25, 1984"--P. ii.
Includes bibliographical references.
ne 15/04/2019
Loan
Keywords: Abstracting and indexing services--Nigeria--Congresses.; Indexes--Congresses.; Indexing--Congresses.; Nigeria